Chaos synchronization in a 6-D hyperchaotic system with self-excited attractor - Ahmed S. Al-Obeidi; Saad Fawzi AL-Azzawi (Universitas Ahmad Dahlan, 2020)
This paper presented stability application for chaos synchronization using a 6-D hyperchaotic system of different controllers and two tools: Lyapunov stability theory and Linearization methods. Synchronization methods based on nonlinear control strategy is used. The selecting controller's methods have been modified by applying complete synchronization. The Linearization methods can achieve convergence according to the of complete synchronization. Numerical simulations are carried out by using MATLAB to validate the effectiveness of the analytical technique.